Self-Recurrent Learning and Gap Sample Feature Synthesis-Based Object Detection Method. (29th September 2021) - Jiang, Lvjiyuan; Wang, Haifeng; Kai Yan,; Zhou, Chengjiang; Li, Songlin; Dang, Junpeng; Chang, Rong; Peng, Jie; Fang, Yanbin; Dai, Chenkai; Yang, Yang
Abstract : Object detection-based deep learning by using the looking and thinking twice mechanism plays an important role in electrical construction work. Nevertheless, the use of this mechanism in object detection produces some problems, such as calculation pressure caused by multilayer convolution and redundant features that confuse the network. In this paper, we propose a self-recurrent learning and gap sample feature fusion-based object detection method to solve the aforementioned problems. The network consists of three modules: self-recurrent learning-based feature fusion (SLFF), residual enhancement architecture-based multichannel (REAML), and gap sample-based features fusion (GSFF). SLFF detects objects in the background through an iterative convolutional network. REAML, which serves as an information filtering module, is used to reduce the interference of redundant features in the background. GSFF adds feature augmentation to the network. Simultaneously, our model can effectively improve the operation and production efficiency of electric power companies' personnel and guarantee the safety of lives and properties.